Interview with Marcus Carter on Children's Play and Games Studies Discourse - Carter, Marcus (Gamevironments, 2021)
In this interview, Dr. Marcus Carter, co-director of the Socio-Tech Futures Lab and Senior Lecturer in Digital Cultures at The University of Sydney, talks about his research on children's play, his views towards discourse on gaming addiction, and games studies discourse.